Editorial: The importance of academic training in emotional intelligence for teachers - Valente, Sabina (2022)
Considering that teaching concerns more than just pedagogical and content knowledge, and that is an emotional practice, teachers must develop emotional competencies. Mayer and Salovey’s model understands emotional intelligence (EI) as a competence that can be learned and developed, and that consists of the adaptive use of emotional information (Mayer et al., 2016). Thus, this Research Topic focuses on the relevance of teachers’ academic training should include EI as an essential competence for all teachers. The aim was to provide empirical evidence that examines the importance of teachers’ EI, as a crucial emotional competence, highlighting recent studies that can contribute to a new model of teacher education (in academic and in-service education).